Identifying photochemical alterations of dissolved pyrogenic organic matter using fluorescence spectroscopy - Jessica K. Egan; Diane M. McKnight; Maggie M. Bowman; Michael D. SanClements; Adrian C. Gallo; Jeff A. Hatten; Lauren M. Matosziuk (Aquatic Sciences, 2023)
Many streams originate in forested watersheds at risk of wildfires. Wildfires can introduce thermally altered organic compounds to terrestrial and aquatic systems. Understanding the degradation of leachates from these burned organic materials, referred to as dissolved pyrogenic organic material (PyDOM), is critical in determining water quality impacts in forested watersheds. This study used fluorescence spectroscopy to examine photochemical alterations of PyDOM generated by leaching organic matter burned at various temperatures. The PyDOM was exposed to natural sunlight for 25 days and the photochemical formation of hydrogen peroxide was monitored. PyDOM was characterized using ultraviolet–visible absorption, excitation–emission matrix (EEM) fluorescence spectroscopy, and fluorescence indices. Throughout the experiment, the emission intensity of the humic peak for all light-exposed leachates decreased while dark leachates exhibited no significant change in their fluorescence spectra. Additionally, hydrogen peroxide concentrations and UV absorbance decreased progressively over time, providing direct evidence that PyDOM concentrations can be significantly reduced by photodegradation. A characteristically low emission peak was observed in the EEMs of the fresh PyDOM, which could help in detecting fresh PyDOM. These results demonstrate that PyDOM derived from burned leachates is susceptible to photodegradation and that fluorescence measurements could be used as proxies for detecting PyDOM immediately post-wildfire.